2019
DOI: 10.3846/cs.2019.6451
|View full text |Cite
|
Sign up to set email alerts
|

The Content and Role of Intrinsic Motivation in Creative Work: The Importance of Seeking “Enjoyment”

Abstract: The present paper assesses the “content” and “role” of intrinsic motivation during the creative production process. Based on semi-structured interviews with 16 light-entertainment television producers-directors in South Korea, it was observed that intrinsic motivation towards creative work included a desire to maintain enjoyment from such activities. Enjoyment was classified into two types: enjoyment based on job expectations and enjoyment based on the actualization of individual creative ambitions. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Overcoming difficulties during project activities fosters stress resistance in students, which many authors consider to be the most important skill that needs to be developed among designers-architects [2,3,14]. Students who have received such experience will not "float" at the first failures in real work, which allows them to gain a foothold in the team [5,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overcoming difficulties during project activities fosters stress resistance in students, which many authors consider to be the most important skill that needs to be developed among designers-architects [2,3,14]. Students who have received such experience will not "float" at the first failures in real work, which allows them to gain a foothold in the team [5,17].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage is also one age category of teams, which allows participants to more freely discuss all emerging issues. The positive aspects of the creative competition allow the participants to enjoy the design process, which contributes to the development of intrinsic motivation during the creative production process [5].…”
Section: Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth narrative is affective. Previous studies have observed that even when underpaid and overworked, creative laborers present high levels of job satisfaction, as they present strong intrinsic motivation (An, 2019; Arvidsson et al, 2010; Hesmondhalgh & Baker, 2011). The editors interviewed also justified a seemingly unfair condition because of the sense of fulfillment they derive from creative labor.…”
Section: Methodsmentioning
confidence: 99%
“…Research on creativity is very diverse because it looks at it from various perspectives. Some research focuses on creative products, cognitive processes and motivational factors behind creative work (An, 2019), contextual factors that affect creativity, and others focus on the relationship between personality and creativity factors (Gino & Ariely, 2012).…”
Section: Introductionmentioning
confidence: 99%